(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Consumption of pesticides poses serious health concerns and a need for reliable and effective detection techniques. Chlorpyrifos has been linked to numerous poisoning incidents, including accidental, suicide, and homicidal ones in India. The impact of chlorpyrifos on human health is influenced by several variables, including the duration, volume, and frequency of exposure, the person’s health, and specific environmental circumstances. Due to their lethal toxicity, forensic toxicology laboratories frequently encounter cases of pesticide poisoning. Herein, a method utilizing VA-DLLME method in conjunction with a TLC image analysis system is presented to detect the presence of chlorpyrifos, an organophosphorus pesticide, in blood. Following the VA DLLME method, a TLC plate was spotted with 20µl of the sample(chlorpyrifos), and this plate was developed by using a mobile phase (ethyl acetate and cyclohexane ,9:1v/v). The developed plate was next imaged under the ultraviolet chamber at 254 nm, and the image was further analyzed by using the free software ImageJ to quantify the spots on the thin layer chromatography plate. The approach was discovered to be linear in the 0.5–10 µg/ spot range under ideal circumstances, with a correlation coefficient of 0.9917 for blood samples and 2-16 µg/spot with a correlation coefficient of 0.9932 for urine, respectively. LOD and LOQ for blood was found 0.93 and